Environmental Social and Governance ( ESG ) ant the portfolio performance : an integrative search for islamic ESG Firm in Indonesia and Malaysia - Abdul_Qoyum (Pascasarjana UIN Sunan Kalijaga Press, 2020)
et,1/irh,c.1